Report of the Treasurer for the Year Ending December 31, 1999 - Hinshaw, C. Elton (American Economic Review, 2000)
The proposed budget for 2000 in Table 1 projects an operating loss of $736 thousand, investment income of $598 thousand, and an overall deficit for the year of $138 thousand.Net